Aspects of cotton and vegetable farmers' pest management decision-making in India and Kenya - Williamson, S.; Little, A.; Arif Ali, M.; Kimani, M.; Meir, C.; Oruko, L. (Informa UK Limited, 2003)
Improvement of farmers' decision-making has been recognised as critical for the implementation of IPM, yet practitioners lack sound knowledge on the 'how and why' of farmers' decision-making processes. This study explored the perceptions, pest management practice, decision tools and sources of information of smallholder farmers growing cotton in India and vegetables in Kenya. Farmers trained under an Insecticide Resistance Management and two IPM Farmer Field School projects were compared with untrained farmers from the same localities, using individual interviews and participatory group analysis methods. Trained farmers' decision-making was enhanced, by the use of more decision tools and new sources of information and technologies and they were generally more confident in their pest management strategies than untrained farmers. As a result, trained farmers reduced their pest management costs but did not always obtain higher gross margins. Issues of gender, sustainability, economics and group action are discussed, along with recommendations for research and extension to take a closer look at farmers' decision-making processes in cash and subsistence crops.